Intervención fisioterapéutica en paciente de sexo femenino de 27 años de edad en estado de gestación con dolor pélvico. - Laje Jarrin, Andreina Marianela (2024)
This clinical case study concerns a 27-year-old pregnant patient who comes to physiotherapy for pelvic pain. The discomfort, focused in the pubic and sacroiliac areas, affects her daily activities. After a detailed evaluation, treatment goals were established to mitigate the pain, improve functionality and promote autonomy in its management. The physiotherapeutic treatment plan included education about pelvic pain, specific exercises to strengthen the pelvic muscles, relaxation techniques and manual therapy, as well as regular follow-ups to adjust the intervention according to the patient's needs. The results showed a notable improvement in both pain intensity and functionality, validating the effectiveness of physical therapy in the management of pelvic pain during pregnancy. The importance of continuing education, exercise and medical follow-up to sustain the gains made and prevent relapses was emphasized. This case highlights the essential role of physical therapy in the management of pelvic pain during pregnancy, thus contributing to improve the quality of life of pregnant women and promoting a more comfortable and healthy pregnancy for both mother and baby.